STRUKTUR GERAK TARI JEPIN LANGKAH BISMILLAH DI KELURAHAN SIANTAN HILIR KECAMATAN PONTIANAK UTARA - Fifilia Sarianti; Ismunandar Ismunandar; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research was influenced by the occurrence of changes in the movement of the Jepin Langkah Bsimillah dance so that the researcher wants to maintain the authenticity of the Jepin Langkah Bismillah dance. This research uses the descriptive method in the qualitative form and uses the choreography approach. The interviewees in this research are Suhaili, Syamsul Watan and Alkhanul Khairat who know about the Jepin Langkah Bismillah dance in Siantan Hilir Village, North Pontianak District. The techniques of data collection used are observation, interviews, and documentation. The data validity testing techniques used are the extension of observation and sources triangulation. Based on the analysis of the data, it can be concluded that the structures of the Jepin Langkah Bismillah dance movements at Siantan Hilir Village, North Pontianak District are as follows: There are 3 types of motion which are described based on the smallest part first, namely the motion motives, motion phrases, sentences of motion and groups of movement that become a unified whole of motions in the Jepin Langkah Bismillah dance. Jepin Langkah Bismillah consists of 108 motion motives, 97 motion phrases, 35 motion sentences and 4 motion groups with tahto as a liaison.Keywords: Motion Structure, Jepin Langkah Bismillah Dance.